2015
DOI: 10.1007/s12032-014-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 pathway induces epithelial–mesenchymal transition through up-regulation of Snail signaling in gastric cancer

Abstract: The chemokine receptor 7 (CCR7) and Snail signaling have been linked to various types of cancers. The associations between these signalings and the epithelial-mesenchymal transition (EMT) are not clear in gastric cancer. Here, the expression of CCR7 and Snail was detected in gastric cancer by immunohistochemistry and Western blot. Meanwhile, gastric cancer cells were subjected to CCL19, si-control, and si-Snail treatment. Cell cycle, migration, and invasion were also analyzed. The expression patterns of CCR7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…A meta-analysis which included 1,697 participants with GC indicated that increased CCR7 expression was associated with negative clinicopathological prognostic factors including deeper tumor invasion and predicted a worse long-term survival outcome (46). The possible underlying molecular mechanism is that CCR7 contributes to TGF-β1-induced epithelial-mesenchymal transition (EMT), facilitating lymph node metastasis in patients with gastric cancer (47,48). Therefore CCR7 may potentially serve as a novel prognostic indicator and a potential target for gastric cancer therapy.…”
Section: Lymphangiogenesis and Metastasismentioning
confidence: 99%
“…A meta-analysis which included 1,697 participants with GC indicated that increased CCR7 expression was associated with negative clinicopathological prognostic factors including deeper tumor invasion and predicted a worse long-term survival outcome (46). The possible underlying molecular mechanism is that CCR7 contributes to TGF-β1-induced epithelial-mesenchymal transition (EMT), facilitating lymph node metastasis in patients with gastric cancer (47,48). Therefore CCR7 may potentially serve as a novel prognostic indicator and a potential target for gastric cancer therapy.…”
Section: Lymphangiogenesis and Metastasismentioning
confidence: 99%
“…In addition, signaling via CCR7 induced chemotactic and invasive responses in CCR7-positive gastric cancer cells, suggesting that functional CCR7 in gastric cancer cells may exert an important role in migration and invasion of gastric cancer. Recently, two groups demonstrated that CCR7 is involved in the epithelial-mesenchymal transition in gastric cancer (44,45). Zhang et al (44) reported that CCR7 induced the epithelial-mesenchymal transition by upregulating Snail, and that Snail signaling was regulated by the ERK and PI3K pathways instead of the Rho pathway, resulting in G 1 /S cell cycle progression, migration and invasion of gastric tumor cells.…”
Section: C-c Motif Ccr7mentioning
confidence: 99%
“…Recently, two groups demonstrated that CCR7 is involved in the epithelial-mesenchymal transition in gastric cancer (44,45). Zhang et al (44) reported that CCR7 induced the epithelial-mesenchymal transition by upregulating Snail, and that Snail signaling was regulated by the ERK and PI3K pathways instead of the Rho pathway, resulting in G 1 /S cell cycle progression, migration and invasion of gastric tumor cells. Ma et al (45) investigated a CCR7-associated mechanism involved in gastric cancer progression, which was predicted on the basis of a bioinformatics analysis and verified in gastric cancer cells and primary tumor tissues.…”
Section: C-c Motif Ccr7mentioning
confidence: 99%
“…After excluding irrelevant articles by reviewing the titles and abstracts of those studies, two investigators (P. Du and Y. Liu) reviewed the full text version of the remaining 30 articles independently in accordance with the inclusion and exclusion criteria. Finally, 15 articles [7][8][9][10][13][14][15][16][17][18][19][20][21][22][23] comprising data on 1697 participants met the requirement of the analysis. The detailed search steps are described in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Many studies have been conducted to understand the relationship between CCR7 expression and clinicopathological features and 5-year overall survival (OS) rate, but a unanimous conclusion has yet to be reached. The prognosis of CCR7 expression in gastric cancer reported by different researchers was contradictory [7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%